Pengaruh Kerjasama Tim dan Persepsi Dukungan Organisasi Terhadap Prestasi Kerja Karyawan - Jaenab Jaenab; I Dewa Nyoman Usadha; Rahmatia Rahmatia (Journal of Business and Economics Research (JBE), 2023)
The purpose of this study was to examine the effect of teamwork and perceived organizational support on work performance at PT. Kawi Cemerlang Bima. This research is a quantitative research and the type of research is associative with an Explanatory Research approach. The population in this study is 36 employees and the sampling technique is that the sample uses a saturated sample while the data collection technique uses a questionnaire, with reference to a 5-point Likert scale and then distributed to 36 respondents have PT. Kawi Cemerlang Bima. The data analysis technique used multiple linear regression analysis and then analyzed with SPSS version 22. The results of this study 1) There is no significant effect of Teamwork on Employee Performance at PT. Kawi Cemerlang Bima. 2) There is a significant influence of perceived organizational support on employee performance at PT. Kawi Cemerlang Bima. 3) There is a significant influence of Organizational Culture and Perceptions of organizational support on Employee Performance at PT. Kawi Cemerlang Bima.